1997
DOI: 10.1093/ije/26.1.14
|View full text |Cite
|
Sign up to set email alerts
|

The increasing incidence of lung adenocarcinoma: reality or artefact? A review of the epidemiology of lung adenocarcinoma.

Abstract: Lung adenocarcinoma is the most common cell type in females (smokers or non-smokers) and in non-smoking males. Its incidence has been increasing in younger cohorts of males and females until very recent years. Changes in classification and in pathological techniques account for some of this increase. In females and non-smoker males, the increase could be partly due to a detection bias in former studies. Nevertheless, successive cohorts over time seem more likely to develop adenocarcinoma and less likely to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
140
1
8

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(163 citation statements)
references
References 87 publications
14
140
1
8
Order By: Relevance
“…Moreover, since low-tar filter cigarette smokers tend to inhale deeply to compensate for reduced nicotine intake, cigarette smoke will reach the more peripheral regions where adenocarcinoma mainly occurs. 43) It is reported that low-tar cigarettes contain a higher level of nitrate and generate a higher level of tobacco-specific nitrosamines, which specifically induce adenocarcinoma in an animal model. 44,45) Also, it was shown in humans that switching from nonfilter to filter cigarettes will reduce the risk of squamous cell carcinoma, but not the risk of adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since low-tar filter cigarette smokers tend to inhale deeply to compensate for reduced nicotine intake, cigarette smoke will reach the more peripheral regions where adenocarcinoma mainly occurs. 43) It is reported that low-tar cigarettes contain a higher level of nitrate and generate a higher level of tobacco-specific nitrosamines, which specifically induce adenocarcinoma in an animal model. 44,45) Also, it was shown in humans that switching from nonfilter to filter cigarettes will reduce the risk of squamous cell carcinoma, but not the risk of adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma is the most prevalent form of lung cancer in younger males (v50 yrs old) and in women of all ages, in never smokers, and in former smokers [26]. Differences in tobacco smoking habits (filters, light tobacco cigarettes, profound inhalation) appear to favour the development of distal bronchiolar and alveolar carcinogenesis at the expense of proximal squamous cell carcinoma [27,28].…”
Section: Adenocarcinomasmentioning
confidence: 99%
“…[1][2][3][4][5][6] It is hypothesized that this trend is mainly due to the dissemination of low-tar filter cigarettes, [7][8][9] since filters mainly remove the larger particles in cigarette smoke, which tend to be deposited in the central large bronchus where most squamous cell carcinomas arise. However, such filters do not remove smaller particles, which tend to reach the peripheral region of the lung where adenocarcinomas arise.…”
mentioning
confidence: 99%